Ventilator integrated polygraphy for patients using non-invasive ventilation; Case report - López-Brull, Helena; Mira-Padilla, Estefanía; Hussein, Sarah; Guerder, Antoine; Wozniak, Estelle; Esteban-Ronda, Violeta; Gonzalez-Bermejo, Jésus (Frontiers in Medicine, 2022)
The COVID-19 pandemic has meant that home respiratory services have needed to be reviewed. As a result, new solutions have been developed and implemented. The Vivo 45™ (Breas, Mölnlycke, Sweden) is a ventilator that offers clinicians the ability to attach effort belts to the device. This allows the clinician to review ventilator traces with the addition of thoracic and abdominal activity. This allows more flexibility for the monitoring of patients at home and in the hospital, with detection of patient ventilator asynchrony (PVA). Decreasing PVA may improve ventilator adherence and increased ventilator usage improves survival. We report 3 cases of patients undergoing overnight monitoring with the Vivo 45™, highlighting the benefit of ventilator integrated polygraphy. In our three cases we demonstrate a simple safe tool to optimize NIV treatment over one or two-night recordings using ventilator downloaded software with the addition of effort belts and pulse oximetry without involving more than one machine and without hospitalization in a sleep unit.